gwp 2017
DOI: 10.24149/gwp317
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Aggregate Effects of Credit Frictions and Uncertainty

Abstract: This paper integrates a financial accelerator mechanism à la Bernanke et al. (1999) and timevarying uncertainty into a Dynamic New Keynesian model. We examine the extent to which uncertainty and credit conditions interact with one another. The idea is that uncertainty aggravates the information asymmetry between lenders and borrowers, and worsens credit conditions. Already poor credit conditions amplify the effect of shocks (to both the mean and variance) on the aggregate economy. In our model, uncertainty mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Chugh () finds a value of 0.037. Finally, Balke, Martinez‐Garcia, and Zeng (), who estimate σS via simulated method moments using aggregate macrofinancial data, find a value of 0.025. Despite the different data and sample period used in different studies, our estimates are close to those found elsewhere in the literature.…”
Section: Calibration and Solution Methodologymentioning
confidence: 98%
See 3 more Smart Citations
“…Chugh () finds a value of 0.037. Finally, Balke, Martinez‐Garcia, and Zeng (), who estimate σS via simulated method moments using aggregate macrofinancial data, find a value of 0.025. Despite the different data and sample period used in different studies, our estimates are close to those found elsewhere in the literature.…”
Section: Calibration and Solution Methodologymentioning
confidence: 98%
“…Finally, Bloom (), Bloom et al. (), Bachmann and Bayer (), and Balke, Martinez‐Garcia, and Zeng () consider both notions of uncertainty.…”
mentioning
confidence: 99%
See 2 more Smart Citations